Effect of the Addition of Solid Particles on the Capacity of Thermal Storage of Nitrate Base Salts (2021)
ABSTRACT: Concentrating Solar Power plants (CSP) is part of the technologies recently developed as one of the alternatives to provide for the high energy demands and the consumption of fossil sources. The main advantage of the CSP plants is the Thermal Energy Storage system (TES) which allows the production of electricity even in the absence of sunlight, achieving a reduction of the Levelized Cost of Energy (LCOE) up to 46% in 2018 compared to the value for 2010. However, the LCOE is still high in comparison with other renewable energies; therefore, researches on the subject focuses on reducing this value and making CSP technology more competitive. Molten salt-based nanofluids (MSBNFs), a stable colloidal suspension of nanomaterials with average sizes < 100 nm in molten salt, have aroused great interest thanks to the significant improvement to the low thermophysical properties of the molten salt currently used as storage fluids in TES or heat transfer fluid (HTF) increase in thermal properties. The specific heat capacity of the molten salt is typically less than 2 J/(g°C) and thermal conductivity less than ~1 W/(m K). However, there is still no consensus regarding the percentage of increase in the thermal properties of nanofluids as well as the mechanisms responsible that. For this reason, this doctoral thesis focuses on the understanding of the effect of nanoparticles on MSBNFs by using Hitec salt as the base fluid and alumina nanoparticles as an additive at three different concentrations, 0.5, 1.0 and 1.5 wt.%, seeking not only to establish the effect on the specific heat capacity but also the aggressiveness of the salt towards metals. In the same way, a new method for the synthesis of MSBNFs is established by replacing the water of the traditional two-step method with butanol in order to guarantee the suspension of the nanoparticles and, in turn, the homogenization of the system. Hence, the thermal characterization, specific heat capacity evaluated by Modulated Differential Scanning Calorimetry, the melting point for Differential Scanning Calorimetry and the thermal decomposition obtained by Thermogravimetric analysis are presented, as well as the evaluation of the corrosive behavior of both the pure salt and the nanofluid with the highest specific heat capacity obtained on an austenitic stainless steel AISI 304, in a test up to 2000 h at 550°C, employing two reactors designed to have temperature control, controlled atmosphere, and continuous mechanical agitation. The thermal and chemical stability of the pure Hitec and the molten salt-based nanofluid during the corrosive behavior evaluation is reported. The results showed a significant increase of the specific heat capacity in all the evaluated samples, up to 18.74% with the traditional two-step method and 14.63% with the new proposed method; in the same way, a reduction of the melting point up to 4.93% and little influence on the decomposition temperature. On the other hand, a less corrosive effect was evidenced for the nanofluid compared to the pure salt, thanks to the penetration of the solid nanoparticles inside the corrosion layer. Additionally, the chemical stability of the salts and the nanofluids during the corrosion tests was assessed, thanks to the characteristic bands of the nitrite ion found in Raman spectrometry. Given the above, the feasibility of applying the proposed synthesis to obtain molten salt-based nanofluids for thermal storage in CSP plants was successfully assessed, as well as the possibility of using these nanofluids without major damage to the system, e.g. tanks, valves and pipelines. All the samples synthesized exhibited an increase in energy storage capacity with a proportional decrease in the cost of storage. However, the water elimination process was not considered in the calculations. For that reason, the time and the energy cost of removing the solvent can be the deciding factor between the traditional and new two-step method. By using a solvent with low vapor pressure, like ethanol, instead of water, the new two-step method may be more adequate than the traditional method. Thereby, the increase of the specific heat capacity, as well as the energy storage capacity by the addition of alumina nanoparticles, it can contribute to a significant reduction in the size of thermal energy storage tanks, which leads to a reduction of LCOE of CSP plants, making it a competitive technology when compared to other renewable energy systems, and even more so to traditional ones.